2015
DOI: 10.1212/wnl.0000000000001774
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment 18 years before clinical diagnosis of Alzheimer disease dementia

Abstract: Objective: To examine the relation of performance on brief cognitive tests to development of clinically diagnosed Alzheimer disease (AD) dementia over the following 18 years in a sample of African Americans and European Americans.Methods: A composite cognitive test score based on tests of episodic memory, executive function, and global cognition was constructed in a prospective population-based sample of 2,125 participants (55% African American and 61% female) aged 65 years and older residing in 4 Chicago neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
155
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(174 citation statements)
references
References 44 publications
(44 reference statements)
7
155
1
Order By: Relevance
“…Prior to the manifestation of symptoms and clinical diagnosis, the neurodegenerative processes have already progressed to a relatively advanced stage with marked synaptic loss and neuronal damage 3. A recent study by Rajan et al has shown that impairment in cognition starts almost 18 years before AD dementia could be clinically diagnosed 4. The distinction between memory decline due to the normal course of aging and early stage AD dementia is so ambiguous that the category of mild cognitive impairment (MCI) has been developed to better characterize the earliest signs of AD 5.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the manifestation of symptoms and clinical diagnosis, the neurodegenerative processes have already progressed to a relatively advanced stage with marked synaptic loss and neuronal damage 3. A recent study by Rajan et al has shown that impairment in cognition starts almost 18 years before AD dementia could be clinically diagnosed 4. The distinction between memory decline due to the normal course of aging and early stage AD dementia is so ambiguous that the category of mild cognitive impairment (MCI) has been developed to better characterize the earliest signs of AD 5.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease is apparent through lexical repetition, marked by smaller, higher frequency vocabulary (Garrard et al, 2005), and can be seen in people's writing 10 -12 years before the disease is diagnosed (Rajan et al, 2015). Iris…”
Section: Testing For Alzheimer's Disease Markers In Richnessmentioning
confidence: 99%
“…Garrard et al, 2005;Van Velzen & Garrard, 2008;Lancashire & Hirst, 2009;Le, 2010;Le et al, 2011) and political figures (Garrard, 2009) has highlighted that Alzheimer's disease may be apparent years or even decades before anyone becomes aware of any symptoms of cognitive deterioration. A recent study suggests that Alzheimer's disease can be seen in people's writing 10 -12 years before the disease is diagnosed (Rajan et al, 2015). To test the hypothesis that thought and language are impacted by depression and apathy and revealed in a person's writing style 12 years before a formal diagnosis of Alzheimer's disease presents, we draw on earlier studies of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Human personality traits such as openness to new experiences 20 and negative affect 21 are, respectively, associated with better and worse neurocognitive performance. Individuals with debilitating neurological illnesses such as Parkinson's disease 22,23 and (by definition) the dementia spectrum including Alzheimer's disease 24 also suffer from marked neurocognitive impairments. Further, early life cognitive performance can predict long-term development of illness, 25 including mortality.…”
Section: Introductionmentioning
confidence: 99%